Ratiometric Electrochemiluminescent Immunoassay for Tumor Marker Regulated by Mesocrystals and Biomimetic Catalyst. (1st April 2016) - Zhang, Qingrong; Dai, Hong; Wang, Ting; Li, Yilin; Zhang, Shupei; Xu, Guifang; Chen, Sihong; Lin, Yanyu
Abstract: In this work, a ratiometric electrochemiluminescent immunosensor on octahedral anatase mesocrystals (OAM) support for the ultrasensitive determination of alpha-fetal protein (AFP) by exploiting chitosan functionalized silver iodide (CS-AgI) as biomimetic catalyst was developed. The proposed system was achieved by choosing luminol and potassium persulfate (K2 S2 O8 ) as promising ECL emitter units, due to the potential-resolved property and maximum emission wavelength-resolved property of them. And OAM with high porosity, oriented subunit alignment and large surface area was adopted to adsorb luminol to form solid state ECL and as affinity support to immobilize abounding antibodies of AFP (Ab) firstly. Furthermore, CS-AgI was found to possess biomimetic catalyst activity, which could catalyze the decomposition of hydrogen peroxide that as the common coreactant both of luminol and K2 S2 O8 and thus the dual ECL responses was amplified. When the biosensor incubated in the mixture solution of CS-AgI labeled AFP (CS-AgI@AFP) and the target AFP, owing to the competitive recognition of the CS-AgI@AFP and the target AFP with Ab, the amount of the CS-AgI@AFP captured by the immobilized Ab reduced with the increasing concentration of AFP, accordingly, the dual ECL responses decreased. Upon the basis of the ratio of ECL intensities at two excitation potentials, this proposed ratiometric ECL strategy achieved ultrasensitive determination for the alpha-fetal protein via competitive immunoreaction with a wide linear detection range of 1 fg/ml to 20 ng/ml and a detection limit was 1 fg/ml.